1986
DOI: 10.1210/jcem-62-4-717
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Thyrotropin and Thyroxine Changes during Recovery from Severe Hypothyroxinemia of Critical Illness*

Abstract: In a prospective study of critically ill hypothyroxinemic we assessed the relationship between serum TSH and T4 during the return of serum T4 to normal during recovery. In this longitudinal study of 60 patients with a variety of critical illnesses, including burns, septicemia, and acute renal failure, serum T4 fell to less than 2.7 micrograms/dl (35 nmol/liter) in 24 patients, of whom 14 survived with return of T4 to normal. A rise in total T4 of more than 1.9 microgram/dl (25 nmol/liter) within 96 h occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
70
1
4

Year Published

1989
1989
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(85 citation statements)
references
References 34 publications
10
70
1
4
Order By: Relevance
“…For this reason free T 4 was also estimated by a second method (ELISA) and the changes were similar. Impairment of thyroxine transportation into tissues or reduced serum clearance rate probably due to low cardiac output from the myocardial dysfunction could explain the 'higher T 4 state' in our group I patients (3 elevation of TSH in association with an increase of T 4 has been described in a number of patients with low T 4 recovering from critical illness due to a variety of causes, including AMI (18). It is noteworthy that TSH rose significantly in the group II of our patients with the better prognosis, indicating a more rapid recovery phase compared with group I.…”
Section: Discussionmentioning
confidence: 65%
“…For this reason free T 4 was also estimated by a second method (ELISA) and the changes were similar. Impairment of thyroxine transportation into tissues or reduced serum clearance rate probably due to low cardiac output from the myocardial dysfunction could explain the 'higher T 4 state' in our group I patients (3 elevation of TSH in association with an increase of T 4 has been described in a number of patients with low T 4 recovering from critical illness due to a variety of causes, including AMI (18). It is noteworthy that TSH rose significantly in the group II of our patients with the better prognosis, indicating a more rapid recovery phase compared with group I.…”
Section: Discussionmentioning
confidence: 65%
“…20,21 Kokei et al found normal FT4 and higher TSH levels in animals with non-thyroidal diseases. 22 In our study, secondary and subclinical hypothyroidism was determined in a significant portion of our patients (52%).…”
Section: Discussionmentioning
confidence: 98%
“…The rise in TSH during recovery consistently preceded that of free T3 and free T4, suggesting that this rise is necessary in some patients to return thyroid hormone homoeostasis to normal during recovery. [16] These data also suggest that group C recovered earlier than group M, but both groups would have recovered by the second week of hospitalization. Compared with the changes after elective surgery, those in patients with shock or injury have a more rapid onset, greater intensity, and longer duration.…”
Section: Discussionmentioning
confidence: 73%
“…[16] Vitek et al [14] proposed a biphasic dysfunctional thyroid response in injured patients, with an initial brief rise in TSH and T3 levels followed by a subsequent reduction within 6-18 hours. In that study, the mean interval between injury and hospital admission was 96±38 min, whereas the corresponding intervals in groups M and C of our study were 47.2±21.8 and 51.5±13.9 min, respectively.…”
Section: Discussionmentioning
confidence: 99%